2011
DOI: 10.4236/iim.2011.34016
|View full text |Cite
|
Sign up to set email alerts
|

Rough Computational Approach to UAR based on Dominance Matrix in IOIS

Abstract: Rough set theory is a new mathematical tool to deal with vagueness and uncertainty. The classical rough set theory based on equivalence relation has made a great progress, while the equivalence relation is too harsh to meet and is extended to dominance relation in real world. It is important to investigate rough computational methods for rough set theory, which is one of the bottleneck problems in the development of rough set theory. In this article, rough computational approach to upper approximation reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…We use the importance of an attribute as heuristic information to design an effective heuristic algorithm to find the best reduct. We prove theoretically that the complexity of our algorithm is less than that of the algorithms in [1,3,4,20].…”
Section: Return R;mentioning
confidence: 93%
See 2 more Smart Citations
“…We use the importance of an attribute as heuristic information to design an effective heuristic algorithm to find the best reduct. We prove theoretically that the complexity of our algorithm is less than that of the algorithms in [1,3,4,20].…”
Section: Return R;mentioning
confidence: 93%
“…Finally, the complexity of Algorithm 5.1 is O(|Attr| 2 |U | 2 ). Consequently, this complexity is better than the complexity of algorithms in [1,3,4,20].…”
Section: Return R;mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, rough set theory has fruitful results in many fields, particularly in approximate reasoning [10], mathematical logic analysis and reduct [11][12][13], building of predictive models [14], decision support system [15][16][17][18][19] and other areas. Many studies have shown that the use of rough set theory not only formulate a clear decision-making projects [12], but also enhance the effectiveness of the research while doing optimization [19,20]. Among them, the research related to education of Qu and Wang [16] provided a basis of personalized teaching strategies in distance learning website by analysis of reduct and attribute significance.…”
Section: Introductionmentioning
confidence: 99%
“…As the computation complexity is too high, the efficiency is extremely low. Some of these methods can not deal with incomplete information system when there are a lot of null values in information systems, and at the same time the knowledge we get may not be reliable [11][12][13][14]. As the result in contrast with the indirect method, the direct method maintains the original structure of information systems, and avoids human subjectivity.…”
Section: Introductionmentioning
confidence: 99%